2012
DOI: 10.1007/s11748-012-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic hernia following coronary artery bypass surgery with the right gastroepiploic artery: case report and literature review

Abstract: We report an unusual case of intrapericardial diaphragmatic hernia 2 years after coronary artery bypass surgery with the right gastroepiploic artery. Herniation through the orifice created for the right gastroepiploic artery caused small bowel strangulation and secondary volvulus requiring extensive small bowel resection due to acute mesenteric ischemia. This case highlights the importance of careful operative management of coronary artery bypass surgery with the right gastroepiploic artery and increases aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, some cases of herniations have been reported, which occurred through orifices for GEA grafts of 2 cm long slit or 1.5 cm hole. 2,3 In our case, the diaphragmatic defect size was 70 × 80 mm; we presumed that the defect had enlarged over 20 years after the initial surgery.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, some cases of herniations have been reported, which occurred through orifices for GEA grafts of 2 cm long slit or 1.5 cm hole. 2,3 In our case, the diaphragmatic defect size was 70 × 80 mm; we presumed that the defect had enlarged over 20 years after the initial surgery.…”
Section: Discussionmentioning
confidence: 71%
“…1 However, there are some reports of diaphragmatic herniation following the ante-hepatic route. 3,4 Shimamura et al 3 demonstrated the lack of clear evidence of the superiority of the ante-hepatic route over the retro-hepatic one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneopericardial hernia may be congenital, arising from the failure of development of the transverse septum [ 1 ], or may follow rupture of the diaphragm after trauma [ 2 , 3 ]. A surgical cause has also been reported [ 4 , 5 ]. Since our patient had a defect of the central tendon of the diaphragm with peritoneopericardial communication and no history of trauma, we concluded that the defect was congenital.…”
Section: Discussionmentioning
confidence: 99%
“…It is very rare in humans. The cause of peritoneopericardial diaphragmatic hernia varies, as some authors have reported [ 1 - 5 ]. We herein report a case of peritoneopericardial diaphragmatic hernia with small bowel strangulation in a 75-year-old Korean man.…”
Section: Introductionmentioning
confidence: 99%